TEXT COMPLEXITY IN SENIOR HIGH SCHOOL ENGLISH TEXTBOOKS: A SYSTEMIC FUNCTIONAL PERSPECTIVE - Putra, Dhani Aldila; Lukmana, Iwa (Universitas Pendidikan Indonesia, 2017)
Textbooks have been considered to play a key role in the processes of education by researchers and educators, and the need to explore the language of textbooks has become increasingly recognized. However, although textbooks are an important learning tool, textbook language and composition have not been widely explored especially from textual perspectives. The purpose of the present study is to investigate text complexity progression in the reading texts of English textbooks published for senior high school students in Indonesia. The nature and rate of that progression are addressed within the framework of Systemic Functional Linguistics. Being largely qualitative, this study examines three consecutive textbooks issued by the Ministry of Education, which are available online for classroom use. Data were collected and sampled from the reading texts found in the textbooks and were analyzed with regard to lexical density, lexical variation and grammatical intricacy in order to find the complexity of the texts. The results of the analyses show that regardless of the inconsistent progression of text complexity within each textbook, there is a consistent pattern of text complexity progression across grade levels. In other words, the lexical density, lexical variation and grammatical intricacy across the textbooks were found to have consistent progression from one grade level to another of which the direction is positive. It could be concluded that in general the language used in the texts becomes increasingly sophisticated, especially at lexical level, in accordance with grade level progression to cater for students’ intellectual development.